Sound-absorbing material based oil palm frond natural fibres - Lay, Sheng Ewe; Weng, Kean Yew; Hai, Song Woon; Zawawi Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Effective noise control is vital for improving living standards, but traditional sound absorbers pose health risks. Natural fibers offer a sustainable alternative, with consistent absorption rates across a broad frequency range. These fibers, widely available in Malaysia, are non-toxic, lightweight, renewable, and eco-friendly, making them an attractive option. The safety benefits of natural fibers further enhance their appeal as sound absorbers, making them an excellent choice for those concerned about environmental impact and personal health. This study will examine the effect of different thicknesses on the acoustic performance of natural fibers from oil palm fronds (OPF). The findings demonstrate that, when material density is 160 kg/m3 , all thicknesses can achieve a good Sound Absorption Coefficient (SAC) of 0.8 or greater within 3600 - 6400 Hz range. However, at 180 kg/m3 density, only the 10 mm thickness sample has SAC of 0.8 or greater, but for 2800 - 6400 Hz range. It is worth noting that, across 0 - 6400 Hz, 10 mm thick and 180 kg/m3 density sample has higher SAC than 160 kg/m3 samples. Nevertheless, for 12 mm, 14 mm, and 16 mm thicknesses, SAC of 160 kg/m3 is higher than 180 kg/m3 after an interception point. Before that interception point, SAC of 160 kg/m3 is lower than 180 kg/m3 . As thickness increases from 12 mm to 16 mm, the interception point decreases from 2100 Hz to 1600 Hz. The research demonstrates that various factors, such as frequency, density, thickness, and fiber structure, impact the acoustic performance of OPF LDF.